Transformative Liminality: A Reading of Genevieve L. Asenjo’s “Pangungumusta mula sa Balaan Bukid” - Ritumban, Raymon D (POETIKA, 2023)
In 2021, Filipino writer Genevieve L. Asenjo published her short story collection titled Ang Itim na Orkidyas ng Isla Boracay. Hailed as “Best Book of Short Fiction in Filipino” during the 40th National Book Awards, it consists of narratives that delve into the entanglement of the Philippines, the United States of America, and South Korea. Specifically, in the story “Pangungumusta mula sa Balaan Bukid” (“Pangungumusta” from hereon), South Korea is imagined as a liminal space for the “migratory,” namely, the migrant workers and refugees. In postcolonial thought, a liminal space is perceived as a threshold, a doorway, or a portal where waiting happens, interactions are exchanged, and decisions are made; and as such, in The Location of Culture, theorist Homi K. Bhabha describes it as an “in-between” space of ambivalence, a “third space” where there is neither self nor other. While existing discussions on migrant workers and refugees tend to focus on identity and mobility, the novelty of this paper lies in its problematization of the transformative point of their interaction: What happens when an Overseas Filipino Worker (OFW) gets entangled with a Palestinian refugee in Seoul? How does their interaction offer new perspective on what a liminal space is? The primary method is a textual analysis of “Pangungumusta” through a postcolonial lens. The author argues that in such entanglement a liminal space becomes transformative; and so, it is that which “naghatid . . . sa isang uri ng kaluwalhatian” (ushered in a kind of glory; Asenjo, 2021: 69). This paper is composed of three primary sections: an introduction of Asenjo and her works, a presentation of the plot of “Pangungumusta” and commentary on its postmodern form, and a discussion of liminal space as imagined in the narrative, concluding that liminality is indeed transformative, that is, as the liminal space spatially brings the characters together, it at the same time spells out their ideological differences, which makes transformation possible.